PENGARUH KOMPRES BAWANG MERAH TERHADAP SUHU TUBUH ANAK DEMAM - Cahyaningrum, Etika Dewi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Fever is the increase of body temperature above normal: when it is > 38Â° C (100.4Â°F) measured at rectal, > 37.8Â° C measured at oral, and > 37.2Â° C (99Â° F) measured on axilla. Lowering fever in children can be done through pharmacological and non-pharmacological treatment i.e. by the use of heat energy through conduction and evaporation methods. The method can be implemented with warm compress or home remedies such as red onion. Warm compress is commonly applied while compress with red onion is rarely used. This study aims to prove the decreased of body temperature on children with fever using red onion compress. This study used pre-experimental research design with one-group pre-post-test approach. Sampling technique used was Purposive Sampling. The samples of this study were children with fever in the Community Health Center of Kembaran I of Banyumas in the periode of May to July in 2017. Univariate analysis was conducted to every variable. Meanwhile, bivariate analysis used Wilcoxon analysis technique. The results showed that there was a difference between the average temperature before and after applying red onion compress 0.734oC. It was noticed that the significance value was 0.000 (Ï <0.005) meaning that there was a significant body temperature difference between before and after applying the red onion compress. In conclusion, red onion compress affects the body temperature on children with fever. Keywords: red onion compress, body temperature, children with fever